Breeding biology of Charybdis (Charybdis)feriatus (Linnaeus) from Mangalore - Babu, K V Ramesh; Benakappa, S; Mohan, K Chandra; Naik, A T Ramachandra (Indian Journal of Fisheries, 2011)
The computed Chi-square values indicated that male and female ratio inpopulation was not significant (P